Avaliação da influência do desgaste termomecânico nas propriedades mecânicas de fios ortodônticos de níquel-titânio termoativados - Camargo, Lívio Bráulio Silva e (2014)
To evaluate the influence of thermal and mechanical wear on the bending strength, topography and surface roughness of orthodontic NiTi wires Thermoset. Materials and Methods: round wire gauge section 0.018 "(0.045 mm) alloy NiTi (nickel titanium), thermoactivated (Dental Morelli, 3M/Abzil, American Orthodontics, Detsply GAC, Ormco) were selected. The samples were subjected to deflection test in a universal testing machine Instron 5965 model, and the atomic force microscope AFM model 5500, after being in thermocycled equipment Thermomechanical Wear Model ER 37000. Data were submitted to ANOVA statistical analysis and Tukey test, beyond the Spearman correlation coefficient with α = 0.05 significance. Results: By applying the deflection test at three points we observed that groups 1 and 4 matching results obtained, while the 2 and 3 equaled each other. The average force exerted by the wire was more pronounced in group 1 (control) than the rest. The wire Morelli which was developed as a higher average strength of the wire AO less developed for all groups. By AFM, the wires of Thermoset Abzil and AO presented the most striking defects and Morelli thermoactivated showed less surface irregularities. The other wires were equal in quantity and severity of surface topographical, changes Conclusion: The test deflection at three points proved to be very effective for the desired goals. Demonstrating the equivalence between the control group and the group that was subjected to thermo-mechanical wear. Wires subjected to for just one wear, thermal or mechanical, proved to release more linear force. All Thermoset wires studied andsubmitted to the AFM, showed irregularities on the surface, with no significant differences between groups. The wires had higher surface smoothness were those who developed higher levels of strength in the load-deflection graph.